Global status report on road safety time for action. (World Health Organization, 2009)
Over 1.2 million people die each year on the world's roads, and between 20 and 50 million suffer non-fatal injuries. In most regions of the world this epidemic of road traffic injuries is still increasing. In the past five years most countries have endorsed the recommendations of the World report on road traffic injury prevention which give guidance on how countries can implement a comprehensive approach to improving road safety and reducing the death toll on their roads. To date, however, there has been no global assessment of road safety that indicates the extent to which this approach is being implemented. This Global status report on road safety is the first broad assessment of the status of road safety in 178 countries, using data drawn from a standardized survey conducted in 2008. The results provide a benchmark that countries can use to assess their road safety position relative to other countries, while internationally the data presented can collectively be considered as a global "baseline"against which progress over time can be measured--Executive summary.